Landing Site Mapping and Lander Localization for Chang’e-5 and Chang’e-6 Lunar Sample Return Missions - K. Di; Z. Liu; W. Wan; Y. Wang; B. Liu; M. Peng; W. C. Liu; J. Wang; X. Deng; H. Zhang; R. Sheng; Z. Yue; et al. (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2025)
Chang’e-5 and Chang’e-6 are lunar sample return missions in China’s lunar exploration program. In these missions, high-resolution landing site mapping and lander localization were performed to support mission operations and scientific investigations of the landing sites. The mapping and lander localization results also provided key information to provenance analysis of the samples. This paper presents a review of the landing site mapping and lander localization techniques and results in the two missions, including landing site topographic mapping using orbital images before landing, landing site topographic mapping using descent images after landing, lander localization, crater mapping and scientific applications, such as surface age determination, lunar chronology function update, and regolith thickness estimation.